The Effect of Public Ownership Portion, Financial Distress, and Long-Term Risk on Voluntary Disclosure - Winasis, Dery Awang; Sari, Shinta Permata (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study seeks to examine the impact of public ownership, financial distress, and long-term risk on the extent of voluntary disclosures made by companies that belong to the property and real estate sector listed on the Indonesia Stock Exchange. Methodology: The data from the 2020–2022 annual reports of real estate and property firms listed on the Indonesia Stock Exchange are used in this study. A sample of 123 companies are chosen using a purposive sampling technique. The hypotheses are tested using SPSS 25's multiple linear regression analysis. Results: The results of this study show that both public ownership and financial distress have a negative effect on voluntary disclosure. Conversely, long-term risk has a significant effect on voluntary disclosure. Applications/Originality/Value: This research endeavors to identify the factors that investors should consider when assessing the performance of a company prior to making investment decisions. From an academic perspective, this research aims to enhance the understanding and knowledge of the subject matter, contributing to the advancement of accounting science, specifically financial accounting. Moreover, the findings may provide valuable insights to companies in their decision-making processes and serve as a reference point for future research.